Cross-cultural adaptation of the English version of the Senior Fitness Test to Spanish (2014)
Background. The physical condition of the elderly is related to health and functional independence. One specific and scientifically valid instrument measuring this parameter is the Senior Fitness Test, of which the original version is in English.Objective. To identify the face validity of the test for use in Spanish language based on the cultural adaptation of the English version.Materials and methods. Descriptive study, for which cross-cultural adaptation to Spanish was performed. This involved translation, evaluation of conceptual equivalence by three bilingual experts, synthesis of observations, calculation of values for the index of agreement and applicability.Results. The overall agreement rate is 0.9485. No disagreements arose between the judges for any of the items, and intelligibility is of 85.2%, according to subjects of different ages and levels of schooling.Conclusions. A version of the Senior Fitness Test adapted to Spanish was obtained. The test is backed up by face validity and comprehensibility, and conserves semantic, idiomatic, and conceptual equivalence to the original version.